Concurrent developmental course of sleep problems and emotional/behavioral problems in childhood and adolescence as reflected by the dysregulation profile. Issue 3 (6th December 2018) - Wang, Biyao; Eastwood, Peter R; Becker, Andreas; Isensee, Corinna; Wong, Janice W Y; Huang, Rae-Chi; Runions, Kevin C; Stewart, Richard M; Meyer, Thomas; Brüni, L G; Rothenberger, Aribert; Zepf, Florian D
Abstract: Objectives: Longitudinal data on the course and relationship of concurrent psychopathology in youth are scarce but are of need for better practical patient care and prevention. This study explores the course of (and relationships over time) between sleep problems and concurrent dimensional difficulties relating to anxiety/depression, attention deficiency, and aggressive behaviors in childhood and adolescence. The latter three may jointly form a broad syndrome, the dysregulation profile. Methods: Young people from the Raine Study, a large community cohort sample ( N = 1625) were followed from age 5 to 17 years. Developmental courses of sleep problems and its concurrent regulatory difficulties were estimated separately and jointly. Results: The majority of adolescents reported low levels of problems and which appeared to be stable over time, while a small group (rates between 7.8% and 10.1%) reported enduring problematic developmental courses. Sleep problems and regulatory difficulties shared a strong association in their development over time (individual's probabilities of having the same courses, i.e. low-low and high-high, were between 89.8% and 92.3%). Furthermore, having persistent sleep problems over time was associated with an increased risk of having regulatory difficulties by approximately 10 times, and vice versa. Conclusion: Findings from this study provide empirical evidence for a strong mutual association in the development of sleep problems and difficulties of dysregulation with emotion, cognition, and aggression. It may be suggested that a positive screening of one such psychopathological dimension should lead to a careful assessment, not only to reduce the problem in question but also to prevent the youth from further problems.